2016
DOI: 10.1177/0149206314530166
|View full text |Cite
|
Sign up to set email alerts
|

Fairness Enactment as Response to Higher Level Unfairness

Abstract: In contrast to the abundance of evidence on employee reactions to manager unfairness, we know very little about factors that predict whether managers will act fairly or not. This paper explores the effect of procedural unfairness that emanates from higher level managers on procedural fairness enactment at lower levels in the organization. We argue that lower level managers can enact both more and less fair procedures in response to higher level unfairness and that this depends on the extent to which lower leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…Finally, we tested the significance of the indirect effect. This requires testing a model in which the moderating effect of transgressor power is mediated by cynicism (Muller et al, 2005;Van Houwelingen et al, 2014). However, given that there are no available options for testing simple indirect effects in such a model (Hayes, 2013;Rucker et al, 2011), we treated transgressor power as the independent variable and transgressor response as the moderator to assess simple indirect effects by following Van Houwelingen et al's (2014) procedure.…”
Section: Figure 3b Forgiveness Level Predicted By the Two-way Interaction Between Cynicism And Apology (Study 2)mentioning
confidence: 99%
“…Finally, we tested the significance of the indirect effect. This requires testing a model in which the moderating effect of transgressor power is mediated by cynicism (Muller et al, 2005;Van Houwelingen et al, 2014). However, given that there are no available options for testing simple indirect effects in such a model (Hayes, 2013;Rucker et al, 2011), we treated transgressor power as the independent variable and transgressor response as the moderator to assess simple indirect effects by following Van Houwelingen et al's (2014) procedure.…”
Section: Figure 3b Forgiveness Level Predicted By the Two-way Interaction Between Cynicism And Apology (Study 2)mentioning
confidence: 99%
“… 4 While usually less drastically expressed, this claim represents conventional wisdom: ‘(P)rocedural fairness has been shown to have substantial effects on virtually all important organizational outcomes’ (van Houwelingen, van Dijke, and De Cremer 2014); ‘A major reason why procedural justice is of interest for political theorists is its ability to lessen the impact of unpleasant decisions’ (Klosko 2000, 210); ‘Findings such as these suggest that experiencing fair procedures builds social values, and these values lead people to feel a long-lasting, personal obligation to accept decisions and support rules’ (Hechter 2013, 20).…”
mentioning
confidence: 99%
“…AMT has become a popular platform for collecting data across the social sciences(Berinsky, Huber, & Lenz, 2012;Rand, Greene, & Nowak, 2012). For instance, studies have used AMT to address issues as diverse as generosity(Cryder, Loewenstein, & Scheines, 2013), cross-cultural variations in work outcomes(Uhlmann, Heaphy, Ashford, Zhu, & Sanchez-Burks, 2013), and procedural justice enactment(van Houwelingen, van Dijke, & De Cremer, 2014). Studies evaluating the validity of AMT have shown that the data obtained are reasonably reliable(Behrend, Sharek, & Meade, 2011;Buhrmester, Kwang, & Gosling, 2011;Paolacci & Chandler, 2014), while representativeness of such samples requires close scrutiny by recruiters (see…”
mentioning
confidence: 99%